2019
DOI: 10.2174/1871527318666190131121827
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Ultramicronized Palmitoylethanolamide Therapy in Patients with Myasthenia Gravis: a Pilot Study to Possible Future Implications of Treatment

Abstract: Background: The cannabinoid system may be involved in the humoral mechanisms at the neuromuscular junction. Ultramicronized-palmitoylethanolamide (μm-PEA) has recently been shown to reduce the desensitization of Acetylcholine (ACh)-evoked currents in denervated patients modifying the stability of ACh receptor (AChR) function. <p> Objective: To analyze the possible beneficial effects of μm-PEA in patients with myasthenia gravis (MG) on muscular fatigue and neurophysiological changes. <p> Method: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…PEA has been reported to be effective in animal models of chronic pain and inflammation as well as in several clinical trials on various pain and inflammatory conditions. [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…PEA has been reported to be effective in animal models of chronic pain and inflammation as well as in several clinical trials on various pain and inflammatory conditions. [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological underpinnings of the likely changes in ACh after either OEA or PEA treatments were unknown, but current evidence hints at a possible role of both lipids in the modulation of ACh and 5‐HT through the engagement of PPARα (Donvito et al, 2017; Melis et al, 2008; Mennella et al, 2019). For instance, it has been demonstrated that activation of α7 nAChRs is associated to the promotion of OEA (Donvito et al, 2017) whereas PEA reduces the desensitization of ACh‐evoked currents (Onesti et al, 2019). However, findings regarding the role of OEA or PEA on ACh modulation are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Since these positive effects appeared after only one week of treatment, it is not surprising that they disappeared one week after the withdrawal of the ultra-micronized PEA. Notably, the antibody titre did not significantly change following PEA treatment [ 101 ], suggesting a possible direct effect of ultra-micronized PEA on nAChRs as already shown in ALS patients. The capacity of PEA to reduce the release of pro-inflammatory cytokines could also be exploited to treat diseases such as sarcopenia, a condition characterized by progressive and generalized loss of skeletal muscle mass and strength combined with low physical performance [ 103 ].…”
Section: Pea In Neuromuscular Alterations and Diseasesmentioning
confidence: 99%
“…Taken together, data obtained from this study showed that PEA add-on therapy slows the disease progression, suggesting that PEA could represent a valid aid to slow respiratory impairment in these patients, thus increasing their life expectancy. In another open-label pilot study, also carried out by Inghilleri’s group at the Policlinico Umberto I in Rome, oral ultra-micronized PEA was administered to a cohort of patients afflicted by myasthenia gravis (MG) [ 101 ]. This autoimmune disease is characterized by the presence of auto-antibodies able to disrupt the physiological function of NMJ.…”
Section: Pea In Neuromuscular Alterations and Diseasesmentioning
confidence: 99%
See 1 more Smart Citation